2008
DOI: 10.1007/s12257-007-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal biotechnology: Carotenoid and glycerol production by the green algae Dunaliella isolated from the Gave-Khooni salt marsh, Iran

Abstract: In this study, carotenoid and glycerol production in two unicellular green algae (aìå~äáÉää~=ë~äáå~ and aK=îáêáÇáë) isolated from the Gave-Khooni salt marsh grown in media containing five different salt concentrations (0.17, 1, 2, 3, and 4 M NaCl) were evaluated under sterile conditions. Algae growth decreased as the medium salinity increased. Optimum growth of aK=ë~äáå~ and aK=îáêáÇáë were obtained at 2 and 1 M NaCl, respectively. As salinity increased, glycerol and carotenoid production were increased in aK=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…It seems that in Dunaliella, osmolyte of main for balancing the extracellular osmotic stress is glycerol, because its intracellular concentration intensively accumulates in response to any osmotic stress such as high medium salinity (Shariati, 2003;Hadi et al, 2008). Also, it shown that its intracellular concentration was linearly related to the medium osmotic pressure (Fig.…”
Section: Osmoregulation and Glycerol Productionmentioning
confidence: 98%
See 3 more Smart Citations
“…It seems that in Dunaliella, osmolyte of main for balancing the extracellular osmotic stress is glycerol, because its intracellular concentration intensively accumulates in response to any osmotic stress such as high medium salinity (Shariati, 2003;Hadi et al, 2008). Also, it shown that its intracellular concentration was linearly related to the medium osmotic pressure (Fig.…”
Section: Osmoregulation and Glycerol Productionmentioning
confidence: 98%
“…The genus Dunaliella contains several species which stand out as being the only eukaryotic and photosynthetic organisms which are able to grow in media containing an extremely wide range of salt concentrations, from 0.05 to 5.5 M NaCl (Avron & Ben-Amotz, 1992), but, optimal growth is different in various species and in order to Hadi et al, (2008) reported that optimal growth of D. salina (Iranian strain) was obtained at 2 M NaCl ( Fig. 2 and Fig.…”
Section: Osmoregulation and Glycerol Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dunaliella species were widely distributed in the world and live in an extremely wide range of habitats [7]. These microrganisms were cultivated in many countries to produce carotenoids [8,9], glycerol [8], proteins and vitamins [10], feeding for fish and human consumption [11,12], biofuel production [13,14] and pharmaceutical formulations [15]. Dunaliella species were also used in bioremediation for removing heavy metals and play an important role in detoxification and accumulation of heavy metals [16][17][18].…”
mentioning
confidence: 99%